(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Two third-grade science courses were examined in this study to see if the 5E Learning Cycle or traditional teaching methods were more effective in enhancing student achievement, interest, and engagement. A three-week 5E Learning Cycle unit and a three-week traditional teaching method unit were completed by both classes. The 5E Learning Cycle units had greater student scores, interest, and engagement than the traditional teaching method components.